Penerapan Algoritma Hybrid Affine Cipher dan RSA Terhadap Sistem Keamanan - Togar Timoteus Gultom (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2021)
The higher the value of a data, the higher the risk of damage or loss of the data. This is understandable, because high-value data is like